2019
DOI: 10.21608/ejnf.2019.75834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E Supplementation on Milk Yield, Milk Fatty Acids Profile and Economical Efficiency in Buffalo Cows

Abstract: he current study was accomplished to determine the effect of pre-calving administration of vitamin E on post-partum performance of buffalo cows. Fifteen pregnant buffalo cows of three years age were divided in to 3 groups: Control, treatment (T 1) and treatment (T 2). Control group were given no treatment, T 1 group was given vitamin E (3000 IU/h/d) whereas; T 2 group was given vitamin E (6000 IU/h/d) before 8 week of expected calving even after calving 4 months. Milk yield were different significantly (P ≤ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Chatterjee (2002) recommended that vitamin E supplementation@ 1000 IU/day should be started at least 30 days before parturition to minimize the cases of mastitis upon parturition and therefore increase in milk yield. Kandil et al (2019) reported significant (P<0.05) increase in milk yield on supplementation of vitamin E (3000 IU/head/day and 6000 IU/ head/day) in varying levels. Oldham et al (1991) proved that supplement with vitamin A (170,000 IU) produced significantly more fat corrected milk (FCM) than those receiving only 50,000 IU.…”
Section: Effect Of Vitamin a And E Supplementation On Metabolic Statusmentioning
confidence: 97%
“…Chatterjee (2002) recommended that vitamin E supplementation@ 1000 IU/day should be started at least 30 days before parturition to minimize the cases of mastitis upon parturition and therefore increase in milk yield. Kandil et al (2019) reported significant (P<0.05) increase in milk yield on supplementation of vitamin E (3000 IU/head/day and 6000 IU/ head/day) in varying levels. Oldham et al (1991) proved that supplement with vitamin A (170,000 IU) produced significantly more fat corrected milk (FCM) than those receiving only 50,000 IU.…”
Section: Effect Of Vitamin a And E Supplementation On Metabolic Statusmentioning
confidence: 97%